Elderly age group patients with COPD continuing to smoke -a problem that cannot be ignored - Vitalii I. Kupaev; Dmitriy A. Osipov (Elsevier, 2020)
Introduction: According to the WHO, 30.9% of the adult population of the Russian Federation are active smokers. From 30% to 43% of smoking patients with COPD are not able to give up nicotine despite the diagnosis and deterioration of health. Most of the publications related to the treatment of COPD do not distinguish smoking patients into a separate group. The purpose of this study is a comparative analysis of the effectiveness of LAMA (Tiotropium bromide and Glycopyrronium bromide) and LABA / LAMA (Olodaterol + tiotropium and Indacaterol + Glycopyrronium bromide). Materials and methods: The study involved 102 patients with a high degree of nicotine addiction and irreversible bronchial obstruction. All the patients were submitted to the treatment of nicotine addiction syndrome on the basis of Otkrytie Medical Center LLC. All the patients continue to receive bronchodilatory therapy. Respondents were divided into two groups: patients who quit smoking and patients who continued to smoke. In turn, each group was divided into two subgroups depending on the drugs being taken - LAMA and LAMA / LABA. As comparison criteria, we selected the dynamics of FEV1 and the dynamics of CAT. Results: As a result of the analysis of the obtained data FEV1 increase was detected in both study groups, regardless of the treatment regimen. FEV1 increase within the group of smoking patients was lower than of those who quit smoking - 11% and 22% respectively (p < .05). CAT dynamics showed a downward trend in both groups. However, the patients who quit smoking demon-strated greater reduction of symptoms during therapy than the smoking patients - -10 and − 1 points respectively (p < .05). No statis-tically significant difference was found either on CAT (p = .31) or spirometry - FEV1 (p = .22) for the LAMA and LAMA / LABA subgroups. Combined therapy (LAMA / LABA) applied to the group of patients who quit smoking found to be more effective than monotherapy (LAMA) both in terms of spirometry (an increase in FEV1 came to 26% and 13% respectively (p < .05)), and the de-gree of reduction of the symptoms (CAT) - -11 and − 5 respectively (p < .05). Conclusion: While maintaining nicotine status, long-acting anticholinergic (LAMA) and combined long-acting bronchodila-tors produce a moderate and comparable effect. Therefore, when choosing the tactics of COPD treatment, it is necessary to take into consideration the current nicotine status of the patient as well as the nicotine addiction degree.